Effect of nano-encapsulated bio-stimulant on the growth, yield, and quality of chilli (Capsicum annuum L.) - Matthews, Stella (2024)
Bio-stimulants have demonstrated significant positive outcomes in enhancing plant health, boosting soil fertility, mitigating the adverse effects of environmental stress on plant growth, improving tolerance to heavy metal contamination in soil, and augmenting crop quality and yield. Limited studies have reported the usage of bio-stimulants in soilless medium to enhance plant growth, yield and quality. There are lack of innovative microbial and plant-based bio-stimulants for soilless cultivation systems. Only scarce information is available on the combined effect of bio-stimulants of various origins. Furthermore, microbial-based bio-stimulants have short shelf-life, which makes them not suitable for soilless systems. The hypothesis of the study is co-application of nano-encapsulated bio-stimulants, specifically endophytic plant growth-promoting bacteria and moringa leaf extract, may positively impact the growth, yield, and quality of chilli plants cultivated in soilless media. The main aim of this study is to evaluate the synergistic effect of nano-encapsulated bio-stimulants consisting of endophytic bacteria and moringa leaf extract in soilless medium.